VIPP1 Has a Disordered C-Terminal Tail Necessary for Protecting Photosynthetic Membranes against Stress . Issue 3 (12th May 2016) - Zhang, Lingang; Kondo, Hideki; Kamikubo, Hironari; Kataoka, Mikio; Sakamoto, Wataru
Abstract : VIPP1 protein, localized to chloroplast membranes as large complexes in Arabidopsis, confers tolerance to hypotonic and heat-shock stresses through its disordered C-terminal tail. Abstract: Integrity of biomembranes is vital to living organisms. In bacteria, PspA is considered to act as repairing damaged membrane by forming large supercomplexes in Arabidopsis ( Arabidopsis thaliana ). Vulnerable to oxidative stress, photosynthetic organisms also contain a PspA ortholog called VIPP1, which has an additional C-terminal tail (Vc ). In this study, Vc was shown to coincide with an intrinsically disordered region, and the role of VIPP1 in membrane protection against stress was investigated. We visualized VIPP1 by fusing it to GFP (VIPP1-GFP that fully complemented lethal vipp1 mutations), and investigated its behavior in vivo with live imaging. The intrinsically disordered nature of Vc enabled VIPP1 to form what appeared to be functional particles along envelopes, whereas the deletion of Vc caused excessive association of the VIPP1 particles, preventing their active movement for membrane protection. Expression of VIPP1 lacking Vc complemented vipp1 mutation, but exhibited sensitivity to heat shock stress. Conversely, transgenic plants over-expressing VIPP1 showed enhanced tolerance against heat shock, suggesting that Vc negatively regulates VIPP1 particle association and acts in maintaining membrane integrity. Our data thus indicate that VIPP1 is involved in the maintenance of photosynthetic membranes. During evolution, chloroplasts have acquired enhanced tolerance against membrane stress by incorporating a disordered C-terminal tail into VIPP1.